New treatments for patients with non‐metastatic castration‐resistant prostate cancer: A nursing perspective. Issue 2 (1st February 2021) - Olivier, Kara M.; Floyd, Rebecca; Smith, Matthew R.; Shore, Neal D.; Sutton, Jennifer
Abstract: Globally, prostate cancer (PC) is a leading cause of death in men. Although androgen deprivation therapy (ADT) is the cornerstone of treatment for the disease, most patients eventually develop castration‐resistant PC (CRPC). Patients with non‐metastatic (nm) CRPC, the earliest clinical manifestation of castration resistance, are at risk of progressing to metastatic CRPC, which is associated with reduced life expectancy and poor quality of life. The nmCRPC treatment landscape has recently been transformed by the approval of three next‐generation oral androgen receptor (AR) inhibitors: apalutamide, enzalutamide and darolutamide. This review addresses available new treatment options for nmCRPC that target the AR, considering the effects of adverse event (AE) profiles and drug‐drug interactions (DDIs) when tailoring patient‐centric treatment to individual need, and discussing management strategies and nursing interventions for patients who experience drug‐related AEs. While no head‐to‐head comparisons of apalutamide, enzalutamide and darolutamide have been conducted to date, all three drugs have demonstrated comparable efficacy and maintained quality of life in phase III clinical trials, with differing AE profiles. The three treatments also demonstrate different potential for DDIs with other common medications that may be taken simultaneously. With the availability of new AR‐targeted options for nmCRPC, oncology nurses play a crucial role in the decision‐making process, educating and supporting patients on managing their PC, and ensuring that they receive the most appropriate treatment. As patients with nmCRPC are largely asymptomatic from their disease (with the exception of urinary/erectile symptoms), maintaining quality of life becomes a major objective when prescribing pharmacotherapy. Therefore, weighing treatment efficacy against the respective drug safety profile and examining the potential for adverse drug interactions with concomitant medications are important clinical considerations. Oncology nurses educate patients on potential treatment‐emergent AEs and their management and serve as advocates to ensure that patients receive optimal care based on their individual therapeutic requirements. They also provide information on available auxiliary services for patients and caregivers. This article provides an overview for the oncology nurse of the efficacy, safety, quality of life and DDI potential of these new AR‐targeted therapies in the nmCRPC setting, highlighting considerations for tailoring patient‐centric treatment to individual need. The importance of the oncology nurse in managing adverse drug reactions associated with ADT and AR inhibitors is highlighted and recommendations provided.